DETERMINING THE MAIN PARAMETERS OF THE EFFICIENCY OF THE TOURISM MARKET AND HOTEL BUSINESS (International Journal of Innovative Technologies in Economy, 2020)
The experience of managers, their traditions, analysis of competitors' marketing costs play an important role in the implementation of marketing activities of facilities. Due to the fact that marketing costs make up a significant part of the budget of facilities, it is necessary to monitor the effectiveness of the marketing strategy, ie the costs of its implementation should always be compared with the results of the work. It also enhances brand loyalty by creating a certain emotional connection between the brand and the consumer. The marketing strategy of a firm operating in a competitive tourism services market should be aimed primarily at establishing long-term relationships with the customer.